No Geographic Correlation between Lyme Disease and Death Due to 4 Neurodegenerative Disorders, United States, 2001–2010 - Joseph D. Forrester; Kiersten J. Kugeler; Anna E. Perea; Daniel M. Pastula; Paul S. Mead (Emerging Infectious Diseases, 2015)
Associations between Lyme disease and certain neurodegenerative diseases have been proposed, but supportive evidence for an association is lacking. Similar geographic distributions would be expected if 2 conditions were etiologically linked. Thus, we compared the distribution of Lyme disease cases in the United States with the distributions of deaths due to Alzheimer disease, amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), and Parkinson disease; no geographic correlations were identified. Lyme disease incidence per US state was not correlated with rates of death due to ALS, MS, or Parkinson disease; however, an inverse correlation was detected between Lyme disease and Alzheimer disease. The absence of a positive correlation between the geographic distribution of Lyme disease and the distribution of deaths due to Alzheimer disease, ALS, MS, and Parkinson disease provides further evidence that Lyme disease is not associated with the development of these neurodegenerative conditions.